Analysis of Factors Influencing the Integration of Artificial Intelligence in Small and Medium-Sized Enterprises in Namangan Region - Mukhtorjon Makhmudov; Doniyorbek Tursunov (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
The main objective of this study was to identify effective approaches for implementing artificial intelligence (AI) technologies in small and medium-sized enterprises (SMEs) operating in the Namangan region. The findings reveal that top management commitment and organizational readiness exert the strongest influence on AI adoption, whereas employee adaptability, external support, and competitive pressure do not show a statistically significant impact. Data were collected from 196 business owners and managers through a Google Forms survey and analyzed using SmartPLS 4. The results enabled the identification of priority areas and practical recommendations for effective AI integration. Additionally, the study outlines future directions for enhancing AI implementation among SMEs in Namangan region.